Moscow Autocracy of XVI - XVII Centuries: Eastern ‘’Despotism’’ or an Early Modern European Monarchy? - Zajcev, Vasilij A.; Penskaya, Tat'yana M.; Podgornyj, Viktor I.; Shabalina, Evgeniya I.; Potapov, Vasily J. (Journal of History Culture and Art Research, 2017)
The article considers the problems related to the peculiarities of the Russian state political and legal development during the early New Time (XVI-XVII centuries) in a comparative-historical aspect against the background of similar processes taking place in neighboring European states. The authors come to the conclusion that, despite certain, dictated by objective reasons (first of all, the conditions for the emergence and subsequent development), there are more common features than the differences between the processes of the political and legal sphere development in Russia and Western Europe. The fact that this community escaped from the view of researchers is related, in the authors' opinion, to the fact that foreign observers, describing the political system of an early Russian state, dealt only with an outer shell, while its internal contents remained if not a secret, then, in any case, a mystery for them. They were not admitted to the Russian political cuisine, and therefore the details of Russian political and legal institution functioning remained unavailable to them.